Preincubation with Sn-complexes causes intensive intracellular retention of 99mTc in thyroid cells in vitro - Wunderlich, G.; Wendisch, M.; Aurich, D.; Runge, R.; Freudenberg, R.; Kotzerke, J. (Nuklearmedizin - NuclearMedicine, 2012)
Technetium radiopharmaceuticals are well established in nuclear medicine. Besides its well-known gamma radiation, 99mTc emits an average of five Auger and internal conversion electrons per decay. The biological toxicity of these low-energy, high-LET (linear energy transfer) emissions is a controversial subject. One aim of this study was to estimate in a cell model how much 99mTc can be present in exposed cells and which radiobiological effects could be estimated in 99mTc-overloaded cells. Methods: Sodium iodine symporter (NIS)- positive thyroid cells were used. 99mTc-uptake studies were performed after preincubation with a non-radioactive (cold) stannous pyro - phosphate kit solution or as a standard 99mTc pyrophosphate kit preparation or with pure pertechnetate solution. Survival curves were analyzed from colony-forming assays. Results: Preincubation with stannous complexes causes irreversible intracellular radioactivity retention of 99mTc and is followed by further pertechnetate influx to an unexpectedly high 99mTc level. The uptake of 99mTc pertechnetate in NIS-positive cells can be modified using stannous pyrophosphate from 3–5% to >80%. The maximum possible cellular uptake of 99mTc was 90 Bq/cell. Compared with nearly pure extracellular irradiation from routine 99mTc complexes, cell survival was reduced by 3–4 orders of magnitude after preincubation with stannous pyrophosphate. Conclusions: Intra cellular 99mTc retention is related to reduced survival, which is most likely mediated by the emission of low-energy electrons. Our findings show that the described experiments constitute a simple and useful in vitro model for radiobiological investigations in a cell model.
Keywords: 99mTc; pyrophosphate; stannous chloride; PCCl3; colony-forming assay; Auger electrons